A Procedure to Construct Exact Solutions of Nonlinear Fractional Differential Equations. (10th March 2014) - Güner, Özkan; Cevikel, Adem C.
Abstract : We use the fractional transformation to convert the nonlinear partial fractional differential equations with the nonlinear ordinary differential equations. The Exp-function method is extended to solve fractional partial differential equations in the sense of the modified Riemann-Liouville derivative. We apply the Exp-function method to the time fractional Sharma-Tasso-Olver equation, the space fractional Burgers equation, and the time fractional fmKdV equation. As a result, we obtain some new exact solutions.